Rare Case of Primary Pleural Spindle Cell Sarcoma in a Young Patient - Palaniappan Inbamuthiah; Rajesh Gupta; Mohamed Alhaj Mustafa; Desh Deepak Idnani; Imad Eldin Ahmed Hamed; Anandi Damodaran (Bengal Physician Journal)
Aim and background: This study presents a rare interesting case of primary pleural sarcoma in a young patient. Case description: A 22-year-old Ethiopian male, with no significant past medical history, presented with fever, dry cough, and right-sided chest pain of 4-day duration. The chest X-ray showed moderate right-side effusion. Pleural tap revealed yellowish slightly turbid fluid that was lymphocyte predominantly exudate with high lactate dehydrogenase (LDH), normal glucose and negative malignant cell cytology. Computerized tomography (CT) chest showed mild-to-moderate right-sided pleural effusion with subsequent underlying right basal lung collapse associated with multiple scattered calcified right pleural plaques. Laboratory investigations interestingly showed high alkaline phosphatase. He presented again after 10 days with a massive right pleural effusion. Diagnostic thoracoscopy was done and a pleural biopsy revealed malignant spindle cells in a haphazard pattern, forming neoplastic bone and osteoid with foci of necrosis. Immunohistochemistry was consistent with malignant spindle cell sarcoma of pleura. Follow-up revealed the patient succumbed to illness within a few weeks before further evaluation and chemotherapy could be done. Conclusion and clinical significance: Primary pleural sarcoma is a rare tumor with a poor prognosis and has little past literature review. Diagnosis might be missed and early thoracoscopic biopsy and immunohistochemistry are usually necessary for diagnosis. Presentation in a young patient, presence of pleural calcification in CT scan, elevated alkaline phosphatase, and evidence of new bone formation in histopathology were interesting and unique features seen in this case.